Reconfiguration of Low Voltage Electricity at Micro Hydro Power Plant (MHP) in Andungbiru - Utomo, Teguh (Faculty of Engineering, Universitas Brawijaya, 2022)
Electricity is a means to support community activities both in efforts to improve welfare and to encourage economic development. The National Electricity Company (PLN) as the state electricity provider has not been able to reach the electricity network in remote villages. Andungbiru Village, Tiris Subdistrict, Probolinggo Regency is one of the areas that install PLTMH (Micro Hydro Power Plants). Due to the increase in load every year, the current conditions of the PLTMH power grid in Andungbiru village experience a more even distribution of R, S, and T phases in units 1 and 2. This situation causes very large voltage drops and loss of power to the channel so it needs to be configured to reset it. Based on the results of network configuration, phase voltage R, S, and T in unit 1 is 7,9136% V, 5,9599% V, and 6,4707% V which was previously 22,3385% V, 18,0570% V, and 47,3622% V. The results of reconfiguring unit 2 networks for falling phase voltage R, S, and T are 2,6957% V, 1,4909% V, and 0,8985% V which were previously 7.3672% V, 17,2237% V, and 13,8929% V. The power loss in unit 1 after reconfiguring the network is 2873,3886 Watts which was previously 20910,9708 Watts and in unit 2 after reconfiguring the network is 221,0193 Watts which is 1749,6933 Watts. The results of network reconfiguration can reduce voltage drop and power loss in low-voltage networks and follow the standard that the maximum voltage drop is 10% of the nominal voltage of 220V.